Bridging the Gap Between Islamic Banking and Social Finance: A Macro-Financial Evaluation of Zakat Governance in Indonesia - Muhammad Yoesoef, Yoesrizal; Fazlurrahman Syarif, Muhammad (Islamic Economics Department, Faculty of Islamic Economics and Business, Sunan Ampel State Islamic University, Surabaya Indonesia, 2026)
Background: Despite the significant potential of zakat as an instrument of socio-economic redistribution, its formal mobilization remains persistently below capacity in many Muslim-majority countries, including Indonesia. This gap raises critical questions about the extent to which Islamic financial development contributes to philanthropic governance. Objective: This study aims to investigate the macro-financial relationship between Islamic banking performance and formal zakat distribution, focusing on the roles of Islamic financing, depositor trust, and bank profitability in shaping national zakat mobilization. Methodology: Using monthly time-series data from January 2016 to December 2024, this study applies the Autoregressive Distributed Lag (ARDL) bounds testing approach to estimate both short-run and long-run dynamics among the variables. Findings: The results confirm the existence of long-run cointegration. Depositor trust emerges as the most influential determinant, with substantially higher elasticity compared to Islamic financing, indicating that institutional credibility is the primary driver of zakat mobilization. In contrast, bank profitability does not exhibit a statistically significant effect, revealing a structural disconnect between commercial performance and philanthropic outcomes. This finding reflects the voluntary nature of corporate zakat within the current regulatory framework, which limits the transmission of financial gains into social redistribution. Conclusion: This study contributes to the literature by providing novel macro-level time-series evidence on the financial–philanthropic nexus in Islamic finance. It extends the application of Signaling Theory and Stakeholder Theory into the domain of Islamic social finance, offering a new analytical framework to explain how institutional trust mediates the relationship between financial intermediation and zakat governance. The study also provides a replicable empirical model for future research across Muslim-majority economies. Practical Implications: The findings highlight the need for coordinated institutional reform. Zakat authorities should strengthen transparency and accountability through integrated digital reporting systems to enhance public trust. Financial regulators are encouraged to formalize corporate zakat through mandatory disclosure frameworks and targeted fiscal incentives, thereby aligning banking performance with philanthropic responsibilities. In parallel, Islamic banks should incorporate zakat governance into their strategic and sustainability frameworks, fostering closer collaboration with zakat institutions to optimize the effectiveness of formal zakat distribution.